Violence and human rights : Situation of isolated indigenous peoples in Brazil (Revista da UFMG, 2023)
The decisions taken by Jair Bolsonaro’s government since the first day of his mandate, in January 2019, have weakened the country’s environmental control policies and contributed to reduced inspection, increased deforestation on public lands and, consequently, the violation of the rights of indigenous peoples. There is a great diversity of contexts for isolated indigenous peoples in Brazil, from small groups to a single individual. These groups are the survivors of successive massacres and are threatened by the spread of disease, and for these reasons avoid contact with other agents at any cost. In addition to the need to ensure that their territories remain protected, the decision itself to live in isolation must be guaranteed in accordance with the already established instruments, including the United Nations Declaration on the Rights of Indigenous Peoples and Convention No. 169 of the International Labor Organization (ILO). Despite the traumatic history of contact, Brazil is the country with the largest number of isolated indigenous peoples in South America, as well as has the oldest public policy in terms of guaranteeing the rights of these peoples to self-determination. The measures presented in this article substantially undermine the protection of the rights of isolated indigenous peoples and obstruct the possibility of advancing or enforcing human rights which are internationally recognised and provided for in domestic law.